Pelatihan Dan Pengembangan Pegawai Di Lingkungan Kementerian Keuangan - Leni Andrayani; Veithzal Rivai Zainal; Lenny Christina Nawangasri; Wisnu W. Hariadi (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
This journal uses a library research method to determine the training and development of employees within the ministry of finance. Human resources are an important factor in an agency or company. The strategic role of the Ministry of Finance in managing state finances needs to be supported by reliable, accountable and competent human resources who can complete tasks effectively and efficiently. Therefore, the Ministry of Finance uses the Kemenkeu Learning Centre (KLC) electronic base which functions for technological advancement in the digital era and conducts training that is not limited by distance and time to make it easier for employees.